EFFORTS TO REDUCE SEXUAL VIOLENCE IN EARLY CHILDREN THROUGH SEXUAL EDUCATION - Muhammad Diaz Rizki; Muhammad Rosyad Cahyadi; Syahreza Muslim; Ikhsan Fadillah; Abdillah Sofwan Aby Kusuma; Mavianti Mavianti (Proceeding International Seminar of Islamic Studies, 2023)
The number of victims of violence against children in the form of sexual violence increases every year. Sex education for children can prevent children from becoming victims of sexual abuse, (Ndari, Hasanah, and Rosyidi 2019). It cannot be denied that young children are very much involved in sexual violence, therefore sexual education is very important for children to reduce sexual harassment. Sexual education can equip children on how they understand their gender, take care of themselves and their limbs, and train children to be able to communicate effectively with their parents. The aims of this study were to find out: (1) efforts to tackle sexual violence against young children through sexual education, (2) Classification of young children involved in sexual violence in an effort to reduce sexual harassment. This study used a qualitative research method with a content analysis approach. The object under study is the community in Sei Sikambing B District, Medan Sunggal. Data collection techniques using the method of observing and noting. The data analysis technique used is content analysis which is used to examine the contents of the document. The results of the study show that sexual violence that occurs in children does not necessarily suffer from violent injuries, there is also because they are currently having an illicit relationship and most of it occurs among adolescents. Victims who are involved in sexual violence are certain to experience psychological disorders and lose self-confidence. Parents' sensitivity to children is very necessary and sexual education from an early age will be more able to help children control themselves so they don't contaminate the future, avoid infectious diseases, have a healthy mind and psyche, communicate fluently, and be more confident in everyday life day.